2015
DOI: 10.1128/jcm.02129-15
|View full text |Cite
|
Sign up to set email alerts
|

M-Protein Analysis of Streptococcus pyogenes Isolates Associated with Acute Rheumatic Fever in New Zealand

Abstract: We applied an emm cluster typing system to group A Streptococcus strains in New Zealand, including those associated with acute rheumatic fever (ARF). We observed few so-called rheumatogenic emm types but found a high proportion of emm types previously associated with pyoderma, further suggesting a role for skin infection in ARF.T wo of the most significant consequences of group A streptococcal (GAS) infection are acute rheumatic fever (ARF) and its sequelae, rheumatic heart disease (RHD). New Zealand has among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 14 publications
4
30
0
3
Order By: Relevance
“…During the first 5 years of the emm59 iGAS disease epidemic, emm59 -specific pharyngitis was rarely observed, leading to the notion that emm59 organisms had a restricted population size [18]. Similarly, emm74 organisms appear to be also very rarely associated with pharyngitis [40]. Thus, a restricted emm74 population size may be 1 reason for the minimal strain genetic variation reported here.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…During the first 5 years of the emm59 iGAS disease epidemic, emm59 -specific pharyngitis was rarely observed, leading to the notion that emm59 organisms had a restricted population size [18]. Similarly, emm74 organisms appear to be also very rarely associated with pharyngitis [40]. Thus, a restricted emm74 population size may be 1 reason for the minimal strain genetic variation reported here.…”
Section: Discussionmentioning
confidence: 92%
“…Similarly, it can be hypothesized that the epidemic emm74 clone has recently been introduced to Canada from elsewhere. Although rare in North America and Europe, emm74 iGAS disease, including clusters of emm74 infections, has been described in Africa, India, New Zealand, New Caledonia, and Hawaii [8, 20, 40, 43–46]. We were unable to obtain isolates or genomic data for emm74 organisms isolated in these other geographic locations to test this hypothesis.…”
Section: Discussionmentioning
confidence: 96%
“…In some tropical areas where ARF is common, GAS carriage and GAS pharyngitis seem to be less common than in temperate areas, but impetigo (a superficial skin infection that results in sores and crusting) caused by GAS occurs at very high levels 167 . In New Zealand, the GAS isolates associated with ARF come from classically skin-associated emm types and emm cluster types 168,169 . These observations, and other data, have led to the hypothesis that GAS impetigo might contribute to the pathogenesis of ARF 46,167 , but no definitive link has been found between the two conditions and no studies on the treatment of GAS impetigo for primary prevention of ARF have been carried out.…”
Section: Diagnosis Screening and Preventionmentioning
confidence: 99%
“…35 The Coalition to Accelerate New Vaccines for group A Streptococcus (CANVAS), a joint initiative between the Australian and New Zealand governments, is tackling these barriers to advance GAS vaccine research. 18 Long-acting penicillins for secondary prevention of ARF The mainstay of secondary prevention of ARF remains intramuscular injections of benzathine penicillin every 28 days for a minimum of 10 years. 36 A longer-acting, less painful way of administering penicillin would overcome some of the avoidance and acceptability issues with the current formulation.…”
Section: Research and Development Of New Technologiesmentioning
confidence: 99%
“…6,12 Recently, a New Zealand molecular epidemiological study using M-protein (emm) cluster typing found that 49% of ARF-associated GAS strains from isolates were emm pattern D (skin pattern) types. 18 Further studies examining the causal link between GAS impetigo and RHD remain a priority if we are to make further progress towards the primary prevention of RHD. 12 …”
mentioning
confidence: 99%